Professional Adaptation of Young Teacher to Work in a Modern School - Valentin Vovk (Pedagogical Discourse, 2021)
The article analyzes the theoretical aspects of the problem of professional adaptation of a novice teacher. The analysis of scientific sources made it possible to clarify the essence and content of the basic concepts of this problem, which include: «adaptation», «professional adaptation», «socio-psychological adaptation», «psychological adaptation», «professional adaptation of the future teacher». The article also identifies the features of professional adaptation of the future teacher, identifies the main difficulties that arise for students in the process of learning in free economic education. The concept of «professional adaptation of the future teacher» is understood as the process of adaptation of the future teacher to professional activity, its conditions, achieving a high level of effectiveness of pedagogical work and compliance between professional aspirations, interests, personality qualities and requirements for the modern teacher.Using the questionnaire R.H.Ismailova to assess the socio-psychological adaptation of secondary school teachers, determined the levels of development of the main components of professional adaptation teachers, namely: attitude to the educational institution, relations between teachers, satisfaction willingness to work conditions, satisfaction with one’s position in the team, attitude to work, attitude attitude to students, attitude to the leader, attitude to the team, on the basis of which it is established general level of professional adaptation.